2003
DOI: 10.1159/000067108
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Air Quality and Occurrence of Multiple Sclerosis Relapse

Abstract: Infectious viruses and bacteria can trigger multiple sclerosis (MS) exacerbations. Seasonally changing concentrations of ambient air pollutants are known to predispose to transmissible infections, to induce systemic immune responses and to enhance existing peripheral inflammation. Ambient air quality and monthly MS relapse occurrence in south-western Finland were compared by multivariate logistic regression. The odds ratio of the risk of a relapse onset was over fourfold (4.143, p < 0.001) when the concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 17 publications
(22 reference statements)
3
79
1
Order By: Relevance
“…Thus, because of the greater prevalence of MS around the largest metropolitan statistical area in GA, Atlanta, and the increasing MS ORs when organized by people per square mile, this study's results suggested a possible role of urban environmental factors in the MS distribution in GA. This coincides with previous studies that suggested that MS rates were positively correlated with per capita income, physicians per capita, steel consumption, and several other characteristics which may increase in cities (Mayer 1981) as well as increased air pollution and other environmental factors (Oikonen et al, 2003). While this relationship was somewhat weak for the self-reported male prevalence rates, it was stronger for the female prevalence rates.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, because of the greater prevalence of MS around the largest metropolitan statistical area in GA, Atlanta, and the increasing MS ORs when organized by people per square mile, this study's results suggested a possible role of urban environmental factors in the MS distribution in GA. This coincides with previous studies that suggested that MS rates were positively correlated with per capita income, physicians per capita, steel consumption, and several other characteristics which may increase in cities (Mayer 1981) as well as increased air pollution and other environmental factors (Oikonen et al, 2003). While this relationship was somewhat weak for the self-reported male prevalence rates, it was stronger for the female prevalence rates.…”
Section: Discussionsupporting
confidence: 91%
“…Few studies have focused on the roles of environmental air in the incidence and progression of MS. One study on this subject was conducted in Finland by Oikonen et al (2003). In this study, the role of ambient air quality was found to be associated with MS prevalence.…”
Section: Other Environmental Factorsmentioning
confidence: 84%
See 1 more Smart Citation
“…To our knowledge, the current study is the first to have looked at potential sources through industrial output and examine childhood exposure and MS risk. In other adult MS studies, increased exposure to larger particulate matter (PM 10 ) was related to both increased risk for MS in adults20, 23 and MS relapse using hospitalization records 18, 19, 24…”
Section: Discussionmentioning
confidence: 99%
“…Although some adult MS studies have suggested a relationship between air constituents and MS,18, 19, 20 not all of the Environmental Protection Agency (EPA) criteria air pollutants have been assessed, including fine PM 2.5 , ground level ozone precursors, and lead. Furthermore, the proximity of MS patients to industrial facilities that release toxic chemicals into the air has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%